Designing organised clusters as social actors: A meta-organisational approach - Evgeniya Lupova-Henry; Samir Blili; Cinzia Dal Zotto (Journal of Organization Design, 2021)
In this paper, we aim at exploring whether and how "organised" clusters can be conceived of as deliberate actors within their contexts. Seeing such clusters as meta-organisations, we suggest that these can make "organisationality" design choices, or decisions regarding full or partial implementation of the five elements constitutive of formal organisations: membership, hierarchy, rules, monitoring, and sanctions. To explore the relationship between clusters' organisationality and actorhood, we conduct two qualitative case studies of organised clusters in Australia. Our findings suggest that clusters can deliberately "construct" themselves both as organisations and social actors. Furthermore, drawing upon the institutional work perspective, we propose that clusters can engage in deliberate identity, boundary, and practice work. However, in doing so, they address both internal and external legitimating audiences. Finally, our findings suggest that clusters' organisationality design choices may influence the locus of their actorhood resulting in more or less collaborative approaches to institutional work.
Keywords: 650; Clusters; Organisationality; Actorhood; Institutional work; Identity work; Boundary work; Practice work; Meta-organisation